2016
DOI: 10.1111/gcb.13348
|View full text |Cite
|
Sign up to set email alerts
|

Regional atmospheric cooling and wetting effect of permafrost thaw‐induced boreal forest loss

Abstract: In the sporadic permafrost zone of North America, thaw-induced boreal forest loss is leading to permafrost-free wetland expansion. These land cover changes alter landscape-scale surface properties with potentially large, however, still unknown impacts on regional climates. In this study, we combine nested eddy covariance flux tower measurements with satellite remote sensing to characterize the impacts of boreal forest loss on albedo, eco-physiological and aerodynamic surface properties, and turbulent energy fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 116 publications
4
71
0
Order By: Relevance
“…This pattern is attributable to the long winter in Mongolia's forest‐steppe region, which largely determines mean annual temperature that lies below freezing point in many regions of the country (Hauck, Dulamsuren, & Leuschner, ). The generally lower temperatures in the grassland‐dominated forest steppe compared to the forest‐dominated landscape may result from higher wind speeds (Kelliher, Leuning, & Schulze, ) and from the higher albedo of grasslands than of boreal forests especially in winter (Li et al., ; Helbig et al., ). Furthermore, the higher aerodynamical roughness of forests compared to grasslands causes a greater potential to heat the air (Baldocchi & Vogel, ).…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is attributable to the long winter in Mongolia's forest‐steppe region, which largely determines mean annual temperature that lies below freezing point in many regions of the country (Hauck, Dulamsuren, & Leuschner, ). The generally lower temperatures in the grassland‐dominated forest steppe compared to the forest‐dominated landscape may result from higher wind speeds (Kelliher, Leuning, & Schulze, ) and from the higher albedo of grasslands than of boreal forests especially in winter (Li et al., ; Helbig et al., ). Furthermore, the higher aerodynamical roughness of forests compared to grasslands causes a greater potential to heat the air (Baldocchi & Vogel, ).…”
Section: Discussionmentioning
confidence: 99%
“…Mean annual air temperature has increased since the 1970s, contributing to accelerated permafrost thaw increasing from 0.19% (of total basin area) per year (1970–2000) to 0.58% per year (2000–2015; Chasmer & Hopkinson, ). The increasing rate of permafrost disappearance has caused the expansion of bogs and fens at the expense of forested peat plateaus at Scotty Creek and across the southern Taiga Plains ecozone (Baltzer et al, ; Chasmer & Hopkinson, ; Helbig, Pappas, & Sonnentag, ; Helbig, Wischnewski, et al, ). Similar landscapes to Scotty Creek are widespread throughout the Canadian and Russian boreal forest (Olefeldt et al, ), with a reported 21% of the global boreal forest classified as lowland forest overlying permafrost or thick overburden (Helbig, Pappas, & Sonnentag, ).…”
Section: Methodsmentioning
confidence: 99%
“…Along its southern limit, permafrost is relatively warm and thin (Smith, Burgess, Riseborough, & Mark Nixon, ). In recent decades, warming air temperatures have accelerated the rate of permafrost thaw (Baltzer, Veness, Chasmer, Sniderhan, & Quinton, ; Chasmer & Hopkinson, ; Grosse et al, ; Quinton, Hayashi, & Chasmer, ), impacting forest composition, structure, and function (Baltzer et al, ; Jorgenson et al, ; Lara et al, ; Sniderhan & Baltzer, ), and thus carbon, water, and energy fluxes (Grosse et al, ; Helbig, Wischnewski, et al, ; Turetsky, Wieder, & Vitt, ). Thawing sporadic discontinuous permafrost, that is, permafrost occurring on <50% of the landscape, can induce surface subsidence, thereby replacing forests on peat plateaus with permafrost‐free peatlands (Baltzer et al, ; Jorgenson et al, ; Lara et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The temporal evolutions of potential temperature (θ m ), mixing ratio of water vapor ( w m ), and mixing ratio of CO 2 ( c m ) within the PBL were simulated with the land surface model coupled with a simple 1‐D clear‐sky PBL model (e.g., Baldocchi & Ma, ; Helbig et al., ). The coupled model also provides T c when simulated θ m , w m , and c m were used for meteorological forcing for the next time step ( T c, P B L ).…”
Section: Methodsmentioning
confidence: 99%